2019
DOI: 10.7759/cureus.5676
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Immunosuppressive Therapy and the Development of Infectious Complications Among Patients with Anti-neutrophil Cytoplasmic Antibody-associated Vasculitis: A Single-center, Retrospective Observational Study

Abstract: IntroductionInfectious complications are the leading cause of death in patients with anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV). However, the relationship between initial immunosuppressive therapy and the development of infectious complications and the details of infectious complications among patients with AAV are uncertain. We thus aimed to determine the association between initial immunosuppressive therapy and infectious complications.Material and methodsForty-seven patients with newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a systemic vasculitis that causes organ injuries, particularly to the kidneys and lungs, making it a life-threatening condition [1][2][3]. Lung injuries present with interstitial pneumonitis and/or alveolar hemorrhage [1][2][3]. In addition, neuritis and/or purpura often develops [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a systemic vasculitis that causes organ injuries, particularly to the kidneys and lungs, making it a life-threatening condition [1][2][3]. Lung injuries present with interstitial pneumonitis and/or alveolar hemorrhage [1][2][3]. In addition, neuritis and/or purpura often develops [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Lung injuries present with interstitial pneumonitis and/or alveolar hemorrhage [1][2][3]. In addition, neuritis and/or purpura often develops [1][2][3]. Rapidly progressive glomerulonephritis caused by necrotizing vasculitis in the glomeruli is one of the important kidney lesions that is often detected in patients who develop AAV, leading to end-stage kidney disease [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that 118 (84.29%) of 140 AAV patients had pulmonary lesions, which is higher than that reported in the literature [12] . Among the 118 patients with pulmonary lesions, 68 (57.63%) patients had a lung infection, which is higher than in other studies [13,14] . We also noted that among the enrolled subjects, 3 patients died due to uncontrolled lung infection.…”
Section: Discussionmentioning
confidence: 54%
“…Early aggressive therapy could certainly improve the outcomes of PRS; however, the associated economic factors might negatively affect our current practice because of the high costs of therapy, such as plasmapheresis, ventilator use, and monoclonal antibody therapy. The currently used induction treatment (cyclophosphamide with high-dose corticosteroids) has significantly improved the outcome of AAV but is associated with high toxicity and infectious complications 21 . Plasmapheresis is a lifesaving therapy in PRS with ANCA-related SVV and DAH 22 or rapidly progressive renal failure (Scr > 500 µmol/L) 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%